2017
DOI: 10.1186/s40478-017-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-induced loss of APP function causes GABAergic depletion in recessive familial Alzheimer’s disease: analysis of Osaka mutation-knockin mice

Abstract: The E693Δ (Osaka) mutation in APP is linked to familial Alzheimer’s disease. While this mutation accelerates amyloid β (Aβ) oligomerization, only patient homozygotes suffer from dementia, implying that this mutation is recessive and causes loss-of-function of amyloid precursor protein (APP). To investigate the recessive trait, we generated a new mouse model by knocking-in the Osaka mutation into endogenous mouse APP. The produced homozygous, heterozygous, and non-knockin littermates were compared for memory, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…To test this hypothesis, we counted the number of parvalbumin-positive GABA neurons in the dentate gyrus of OSK-KI mice. As we expected, compared with non-KI mice, only homo-KI mice showed a decrease of GABA neurons at 4 months [64] (Figure 5A). It has been shown that Aβ production depends on neuronal activity [66,67] and that the secreted Aβ, in turn, regulates synaptic activity [68].…”
Section: Mechanism Of Recessive Inheritance Of the Osaka Mutationsupporting
confidence: 83%
See 4 more Smart Citations
“…To test this hypothesis, we counted the number of parvalbumin-positive GABA neurons in the dentate gyrus of OSK-KI mice. As we expected, compared with non-KI mice, only homo-KI mice showed a decrease of GABA neurons at 4 months [64] (Figure 5A). It has been shown that Aβ production depends on neuronal activity [66,67] and that the secreted Aβ, in turn, regulates synaptic activity [68].…”
Section: Mechanism Of Recessive Inheritance Of the Osaka Mutationsupporting
confidence: 83%
“…Thus, to activate GABAergic neurotransmission, we orally administered diazepam, a positive allosteric modulator of GABA A receptor, to 6-month-old homo-KI mice for 2 months and examined their memory and Aβ oligomers at 8 months. While the number of GABA neurons in the dentate gyrus remained lower, cognitive function was recovered and Aβ oligomers were not detected in the treated mice [64]. Taken together, our findings indicate that the Osaka mutation primarily causes a loss of APP function that is essential for GABA neurons ( Figure 5B).…”
Section: Mechanism Of Recessive Inheritance Of the Osaka Mutationmentioning
confidence: 59%
See 3 more Smart Citations